2015
DOI: 10.1111/jvec.12162
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition substrate in Asian tiger mosquito surveillance: Do the sizes matter?

Abstract: Ovitraps are regarded as a reliable system to monitor Aedes albopictus dynamics. However, the dimensions of the oviposition substrate are not standardized, and no studies have investigated which should be the most effective sizes. In this study, the effect of paddle sizes in tiger mosquito egg collection was evaluated. Egg count and density on the wide surfaces and margins of different-sized oviposition substrates have been evaluated in two studies (A and B). In study A, a total of 29,995 Ae. albopictus eggs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was observed that the ovipositing females preferred physical hydrogels to control, whereas the crosslinked hydrogels showed a repellent effect (almost no oviposition), probably due to smooth surfaces and Cl residuals from the crosslinking process, which are already known as deterrents for Aedes albopictus oviposition [ 60 , 78 , 79 , 80 ]. In particular, it was found that a 2-Hydroxyethylcellulose-based hydrogel formulation (HEC16) containing 16 wt% of polymer can attract ovipositing tiger mosquitoes more than control.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the ovipositing females preferred physical hydrogels to control, whereas the crosslinked hydrogels showed a repellent effect (almost no oviposition), probably due to smooth surfaces and Cl residuals from the crosslinking process, which are already known as deterrents for Aedes albopictus oviposition [ 60 , 78 , 79 , 80 ]. In particular, it was found that a 2-Hydroxyethylcellulose-based hydrogel formulation (HEC16) containing 16 wt% of polymer can attract ovipositing tiger mosquitoes more than control.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analyses mitigates the risk of human error in detecting a small number of specimens of an invasive species that are obscured by many 1,000s of larvae from endemic species [64]. Hatching eggs to 1 st instar larvae prior to RT-PCR analysis removes requirements for a specific ovitrap format (design, size, material), ovistrip size [65] or substrate (e.g., cloth, paper, germination paper, wood). Shipment of large numbers of egg samples by postal service is also potentially more logistically viable than couriering water samples for newly developed environmental DNA analysis [66].…”
Section: Discussionmentioning
confidence: 99%